PENERAPAN BIMBINGAN TERSTRUKTUR SEBAGAI UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MELAKSANAKAN PENILAIAN KURIKULUM 2013 DI SDN 011 BERINGIN JAYA - Marwin Saad (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The purpose of this study is to improve teacher competence in carrying out the 2013 curriculum assessment on aspects of knowledge through structured guidance. The research method in this study is School Action Research which consists of planning, action, observation, reflection. The subjects of this study were 16 teachers of SDN 011 Beringin Jaya, with 5 male teachers and 11 female teachers. The results showed that structured guidance can improve teacher competency in implementing the 2013 curriculum assessment on aspects of knowledge with an average of 69.79 in the first cycle which included sufficient criteria, on average in the second cycle of 87.5 with very good criteria, and experienced an increase in the third cycle to 92.18 which was included in the criteria very well.